ANALISIS KINERJA ORGANISASI KELURAHAN GEDAWANG KOTA SEMARANG - Tedi Tri Ramana; Maesaroh Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
The purpose of this study is to; 1) to analyze the performance of Kelurahan Gedawang; 2) to know the inhibiting factors of organization performance of Gedawang Urban Village; and 3) to know the supporting factor of organizational performance of Kelurahan Gedawang Kota Semarang.This research uses qualitative approach with in-depth interview method. The theory used to describe the performance of the Kelurahan Gedawang organization is from Bernardin, which divides the performance based on 6 (six) criteria, namely; Quality, Quantity, Timeliness, Cost-effectiveness, Need for supervision, and Interpersonal impact. While narasumner used as many as 5 (five) people, namely Head of Kelurahan Gedawang; Secretary of Kelurahan Gedawang; Head of Public Service Section of Kelurahan Gedawang; Head of Community Welfare Section of Kelurahan Gedawang; and Head of Community Empowerment and Development Section of Kelurahan Gedawang. The finding of this research is that in doing service to society, can be seen from 6 (six) dimension of performance used by measure. From the quality dimension, the performance of the apparatus has not met the target. The quantity dimension shows that of the 43 planned activities, there are 37 activities that have been realized. The dimension of timeliness shows some of the programs already and is still ongoing, such as the making of tourist forests equipped with mushala, tennis and volleyball courts, tool warehouses, and workhouses; from the visible dimension of the lack of signage (guided explanation of the place) in Gedawang Village, making it difficult for people outside Gedawang to find the location in question. From the dimension of Need for supervision, it appears that the funds already allocated and already spent on tourism forests have turned out to be ambiguous due to the decline of Forestry Minister Regulation which prohibits that forests and zoos are managed by the government, even though they have absorbed substantial funds. From the dimensions of Interpersonal impact looks pretty good because it is able to attract private parties to help build a playground in the Village Gedawang. The existence of corporations in Semarang city that quite a lot, especially in Kelurahan Gedawang, has contributed positively to improving the performance of Kelurahan Gedawang. CSR assistance from the company proved to be very helpful in the construction of facilities and infrastructure in Gedawang Urban Village, specifically related to the protection of nature and the environment. The support also comes from the potential of Gedawang Urban Village, which still upholds mutual cooperation in doing all aspects and areas.